Diaphragmatic dysfunction at the first visit to a chest diseases outpatient clinic in 500 patients with amyotrophic lateral sclerosis. Issue 5 (25th February 2021) - Pihtili, Aylin; Bingol, Zuleyha; Durmus, Hacer; Parman, Yesim; Kiyan, Esen
Abstract: Introduction: In this study, we aimed to evaluate diaphragmatic dysfunction (DD) by using a practical approach in patients with amyotrophic lateral sclerosis (ALS) at the first visit to a chest diseases outpatient clinic. Methods: Patients with ALS seen in our outpatient clinic for the past 5 y and followed up for at least 1 y, were retrospectively evaluated. Having at least one of the following three criteria was accepted as DD: (a) paradoxical abdominal movement (PAM), (b) sitting‐supine forced vital capacity (FVC) difference ≥ 20%, (c) sitting‐supine arterial oxygen saturation measured by pulse oximetry (SpO2 ) difference ≥ 4%. Respiratory symptoms, arterial blood gas analysis, sleep studies, noninvasive mechanical ventilation use, and mortality were recorded. Results: Five‐hundred patients with ALS were included (female/male: 220/280, age: 58.9 ± 11.3 y). Of the patients, 22.8% had daytime hypercapnia. DD was observed in 55% of the patients (PAM in 112, sitting‐supine FVC difference ≥ 20% in 50, and sitting‐supine SpO2 difference ≥ 4% in 113 patients). Of the patients with DD, 31.6% (n = 87) had no respiratory symptoms, 46.4% had FVC > 70% and 33.5% had FVC <50%. Nocturnal hypoxemia (sleep time spent with SpO2  < 90% ≥30%) was present in 59.7%, and all patients with nocturnal hypoxemia had DD. Obstructive sleep apnea (8 severe, 14 moderate, 39 mild) was detected in 55% of the patients with polysomnography (n = 61) or polygraphy (n = 50). During follow‐up, 52.2% of the patients died. Mean survival time was shorter in patients with DD ( P  < .001). Conclusion: Paradoxical abdomimal movement (PAM), sitting‐supine SpO2 difference ≥ 4% and sitting‐supine FVC difference ≥ 20% are indicators of DD, which should be routinely evaluated at every outpatient visit.